Physical and electrochemical properties of 1-(2-hydroxyethyl)-3-methyl imidazolium and N-(2-hydroxyethyl)-N-methyl morpholinium ionic liquids - Yeon, SH; Kim, KS; Choi, S; Lee, H; Kim, HS; Kim, H (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Various ionic liquids (ILs) were prepared via metathesis reaction from two kinds of 1-(2-hydroxyethyl)-3-methyl imidazolium ([HEMIm](+)) and N-(2-hydroxyethyl)-N-methyl morphorinium ([HEMMor](+)) cations and three kinds of tetrafluoroborate ([BF4](-)), bis(trifluoromethanesulfonyl)imide ([TFSI](-)) and hexafluorophosphate ([PF6](-)) anions. All the [HEMIm](+) derivatives were in a liquid state at room temperature. In particular, [HEMIm][BF4] and [HEMIm][TFSI] showed no possible melting point from -150 degrees C to 200 degrees C by DSC analysis, and their high thermal stability until 380-400 degrees C was verified by TGA analysis. Also, their stable electrochemical property (electrochemical window of more than 6.0 V) and high ionic conductivity (0.002-0.004 S cm(-1)) further confirm that the suggested ILs are potential electrolytes for use in electrochemical devices. Simultaneously, the [HEMMor](+) derivatives have practical value in electrolyte applications because of their easy synthesis procedures, cheap morpholinium cation sources and possibilities of high Li+ mobility by oxygen group in the morpholinium cation. However, [HEMMor](+) derivatives showing high viscosity usually had lower ionic conductivities than [HEMIm](+) derivatives. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: ROOM-TEMPERATURE; SALTS; TETRAFLUOROBORATE; AIR